Uselessness of Pleasure: Music and Vanity of Life - Cañas Pérez, Alberto (Eikón / Imago, 2016)
The concept vanitas has been present to the course of History of Art, being the base of a gender whose main message was about despising earthly life, because our only certainity is our own death. This gender was developed due to a variety of simbolic objects, such as skull, flowers, clocks and last but not least, musical instruments. This article will try to demonstrate the importance of this gender and its elements in the Middle Ages and Modern Age, focusing on the presence of musical instruments. To finish, it will be showed the musical iconographical analysis of two vanitates paintings belonging to the so called Spanish Golden Age, as an example of another point of view to analize this kind of pictures.